Analisis Penerapan Unit Dose Drugs Dispensing Sistem (UDDDS) berdasarkan Teori Survey Quality (Servqual) di Instalasi Farmasi Rawat Inap Rumah Sakit “X” - Panuturi Novrianto; Elise Garmelia; Sakti Brata Ismaya (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This study aims to analyze the implementation of the Unit Dose Drugs Dispensing Sistem (UDDDS) based on the SERVQUAL theory at the Inpatient Pharmacy Installation of RS “X”. The research method used a quantitative design with SERVQUAL questionnaires given to pharmacists and nurses, supplemented by in-depth interviews to explore perceptions of the UDDDS implementation. Data analysis was conducted using univariate, bivariate, and multivariate methods. The results of the study indicate that all SERVQUAL dimensions significantly influence the quality of UDDDS services. Based on multiple linear regression analysis, the dimension of Assurance had the most dominant influence on service quality, with a B value of 8.464 and a contribution of 35%. This was followed by Empathy (B = 7.475, 31%), Tangibles (B = 7.547, 28%), Responsiveness (B = 4.847, 20%), and Reliability (B = 3.475, 16%). These findings suggest that the Assurance dimension, which includes trust and confidence in healthcare professionals, plays a crucial role in improving service quality at the Inpatient Pharmacy Installation. Overall, the findings indicate a significant relationship between the implementation of UDDDS and improvements in hospital service quality, particularly in terms of timely medication administration, reduced medication returns, and increased healthcare worker satisfaction. The reduction in medication returns reflects the efficiency of the drug distribution sistem, while the increased satisfaction of healthcare workers shows that UDDDS contributes to better service quality. These findings emphasize the importance of strengthening the Assurance dimension through improving the competence, ethics, and professionalism of healthcare workers. Additionally, integrating UDDDS into the hospital's quality indicators is essential for establishing a sustainable quality culture. This will support the overall improvement of service quality at the hospital.